Critically Appraised Topic on Low-Level Laser Therapy (LLLT) in Dogs: An Advisable Treatment for Skin Diseases? - Roberta Perego; Martina Mazzeo; Eva Spada; Daniela Proverbio (Veterinary Sciences, 2022)
Low-level laser therapy (LLLT) is a therapeutic option that stimulates cellular function through intracellular photobiological and photochemical reactions, promoting better tissue repair and an anti-inflammatory, antibacterial, and analgesic effect. Previous studies in human and veterinary medicine have shown the clinical efficacy of LLLT in many fields. In this study, the literature was reviewed using the critically appraised topic (CAT) method to determine the canine skin diseases for which LLLT is an advisable treatment. A meticulous literature search revealed 19 significant clinical trials, which were critically analyzed. The evaluation of the best accessible evidence in July 2022 suggests that fluorescence biomodulation (FBM), a type of LLLT, can, in combination with systemic antibiotic therapy, be a promising and effective adjunctive treatment for canine interdigital pyoderma and canine deep pyoderma. Furthermore, the evidence suggests that the use of LLLT is not recommended as a therapy for pedal pruritus secondary to canine atopic dermatitis. For other canine skin diseases included in the CAT, although LLLT appears to be a promising treatment, there is not yet good scientific evidence to recommend its use.